Sanatorzy kontra Sikorszczycy, czyli, : Walka o wladze na uchodzstwie w Rumunii 1939-1940 - Dubicki, Tadeusz; Rostworowski, Stanislaw Jan.; Dubicki, Tadeusz (Warszawa : Adiutor, 1993)
An account of the fight for authority within the factions of the Polish government-in-exile while in flight through Romania in 1939-40.
Includes bibliographical references (p. 147-149) and index.
Keywords: Pilsudski, Jozef, -- 1867-1935.; Sikorski, Wladyslaw, -- 1881-1943.; World War, 1939-1945 -- Governments in exile; Poland -- Politics and government -- 1918-1945.